Globalization of Labor Markets and the Growth Prospects of Nations - Basu, Kaushik (World Bank, Washington, DC, 2016)
The many and varied crises in the world economy since 2007 seem to have different origins and diverse manifestations. This paper contends that there is however a structural shift beneath the global economy that is now reaching a critical mass, and that accounts for many of these crises, despite the diversity of manifestations. This shift is occasioned by two kinds of technological changes--the familiar labor-saving and what is here called "labor-linking." The paper argues that these changes (1) create a short-term window of opportunity for developing and emerging economies, but (2) in the long run constitute a major, multilateral policy challenge for all. To meet this challenge, we have to think outside the box and conceive of innovative policies. The paper briefly speculates on what those policies might be.